Ghost island : - Seeck, Max, 1985- (A ghosts of the past novel, 2024)
"The fourth novel in the New York Times bestselling Ghosts of the Past series featuring homicide detective Jessica Niemi! Jessica Niemi is ordered to go on paid leave after a violent altercation, and she decides to travel to a small island in the Åland archipelago to escape attention and find some peace. Meanwhile, a group arrives on the island, and Jessica learns that they are the remaining members of the Doves, people who had to flee from Finland to Sweden during World War II and ended up living in an orphanage on the very same island. Jessica soon hears a local legend about a girl who also inhabited the orphanage. Every night at two o'clock, the girl would put on her blue coat and stand on the pier, looking out at the dark water. One night she disappeared and was never found. Not long after Jessica hears the story of the girl in blue, one of the remaining Doves dies. Jessica soon finds out that two other people have mysteriously died on the island, and they all seem to have something to do with the missing girl. Jessica can't be sure whether she's facing a killer or-just like the legend says-the ghost of the girl in the blue coat. While battling her own demons, uncertain what is real and what is not, Jessica searches for the truth to keep from becoming the next victim"--